Structural Preferences in Phosphanylthiolato Platinum(II) Complexes. Issue 1 (February 2016) - Duran, Josep; Polo, Alfonso; Real, Julio; Benet‐Buchholz, Jordi; Solà, Miquel; Poater, Albert
Abstract: Invited for this month's cover picture are the groups of Prof. Alfonso Polo and Dr. Albert Poater at the Universitat de Girona, as well as their collaborators from the Universitat Autònoma de Barcelona and the Institute of Chemical Research of Catalonia. The cover picture shows phosphanylthiolate ligand coordination on a platinum(II) center to give only the bischelate cis ‐P, P isomer when the ligand/Pt ratio is 2, whereas a trinuclear unexpected complex is achieved with a ligand/Pt ratio of 1. Here, the synthesis and structural determination is combined with density functional theory (DFT) calculations to rationalize the reaction mechanistically and through conceptual DFT. The exciting point of this study is that it opens the door to test new experimental pathways to monitor the preferred cis or trans arrangement of bidentate ligands to platinum. (Legend: H‐white, C‐black, P‐purple, S‐yellow, Cl‐green, Pt‐blue.) For more details, see the Full Paper onp. 51 ff. Abstract : "The stereochemistry of these complexes has particular importance, as different stereoisomers could present a different behavior in a given process. The main goal of the study was to unravel the mechanism of phosphanylthiol coordination to platinum(II)." Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding article onp. 51 ff.